Directive Illocutionary Acts Found in Encanto Movie - Dewi, Ni Kadek Sindia; Komang Dian Puspita Candra; I.G.B. Wahyu Nugraha Putra (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
Directive speech act refers to a verbal action that aims to convince other social actors to take certain actions. This study analyzed the directive speech act especially the types and meanings that found in Disney’s movie entitled Encanto. Qualitative method was applied in conducting this research. Moreover, two theories that proposed by Yule (1996) and Leech (1981) were used in identifying the types and analyzing the meanings of directive speech act in Encanto movie. This study presented the findings regarding to the types of directive speech act such as request, orders, command, and suggestion. On the other hand, the meanings of directive speech act were consisted of social, denotative, thematic, and connotative meanings. In addition, this research also used Halliday and Hassan’s theory (1985) as supporting theory in analyzing the context of situation. The research data were collected through observation method and presented both formally and informally.